Efektivitas Pengawasan ITWASDA terhadap Pengaduan Online dalam Meningkatkan Profesionalitas dan Kepastian Hukum di Polda Kalimantan Barat - Sigit Jatmiko; Edi Saputra Hasibuan (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2026)
This study examines the effectiveness of the Regional Inspectorate for Supervision (Itwasda) in overseeing online-based public complaints at the Regional Police of West Kalimantan in enhancing professionalism and legal certainty. The background of this research is rooted in the rapid development of digital technology, which has driven the transformation of public services through e-policing systems, yet has not been adequately supported by optimal supervisory mechanisms. Normatively, public complaints are regulated under Law Number 25 of 2009 on Public Services and the Chief of Police Regulation Number 9 of 2018 on Public Complaints. This research employs an empirical legal method with a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that the online complaint system has improved public access to reporting cases, particularly those related to online fraud, land disputes, and abuse of authority. However, the effectiveness of supervision remains relatively low, as only approximately 45% of complaints have been fully resolved, 35% are still in process, and 20% lack clear resolution. This condition reflects a gap between legal norms and practical implementation, particularly in terms of legal certainty and accountability. The main contributing factors include limited human resources, weak technological integration, difficulties in verifying electronic evidence, and inadequate coordination and transparency among units. Furthermore, organizational culture also influences the effectiveness of supervision. The implications of these findings suggest that the digitalization of complaint systems has not yet fully ensured substantive justice, as emphasized in progressive legal theory. Therefore, strengthening supervisory systems, enhancing human resource capacity, and improving technological.